2023
DOI: 10.17161/kjm.vol16.18742
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a Novel Activity-Based Checks (ABC) Functional Pain Scale in the Postoperative Urologic Surgery Patient

Abstract: Introduction. The authors investigated a novel functional pain scale, the Activity-Based Checks (ABCs) of Pain, following open urologic surgery. The primary objectives were to establish the strength of the correlation between the ABCs and the numeric rating scale (NRS) and determine the impact of functional pain on the patient’s opioid requirements. We hypothesized that ABC score would correlate strongly with NRS and that the ABC score during hospitalization would be more closely correlated with the number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(32 reference statements)
0
0
0
Order By: Relevance
“…A recent meta-analysis have shown that pain cannot fully explain the decrease in quality of life in patients with osteoporotic fractures [3]. Pain is difficult to assess in cognitively impaired patients with osteoporotic vertebral fractures, and the validity of pain assessments may be questionable [11][12][13][14][15][16]. The International Association for the Study of Pain recommends verbal communication tools such as selfreport assessments for patients with early cognitive memory decline [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis have shown that pain cannot fully explain the decrease in quality of life in patients with osteoporotic fractures [3]. Pain is difficult to assess in cognitively impaired patients with osteoporotic vertebral fractures, and the validity of pain assessments may be questionable [11][12][13][14][15][16]. The International Association for the Study of Pain recommends verbal communication tools such as selfreport assessments for patients with early cognitive memory decline [4].…”
Section: Introductionmentioning
confidence: 99%
“…Many of these patients who have been hospitalized experience cognitive decline. Optimizing pain assessment tools for patients with cognitive decline is an important issue in acute medical care for providing adequate pain relief and rehabilitation of osteoporotic vertebral fractures [11,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%